Multiple large shareholders and corporate environmental protection investment: Evidence from the Chinese listed companies - Feng Wei; Lei Zhou (China Journal of Accounting Research, 2020)
Agencies can reduce problems by adopting a governance structure of multiple large shareholders. However, multiple large shareholders may collude, thereby reducing the behavior that can create long-term value for the company. This paper uses a sample of companies listed on the Shenzhen and Shanghai stock exchanges between 2008 and 2017 to investigate the relationship between multiple large shareholders and corporate environmental protection investment (CEPI). We find that multiple large shareholders will significantly reduce CEPI. Specifically, external supervision and a company's ownership structure affect the relationship between multiple large shareholders and CEPI. In addition, after participating in SOEs, non-state-owned shareholders will significantly improve CEPI of SOEs.
Keywords: 650; Multiple large shareholders; Corporate environmental protection investment; SOEs; Ownership structure